Evaluation of Cladosporium sp. Mycoparacites as Biocontrol Agents of White Rust Disease on Chrysanthemum - Evi Silvia Yusuf; Kurniawan Budiarto; Indijarto Budi Rahardjo (AGRIVITA, Journal of Agricultural Science, 2019)
Cladosporium is a promising mycoparasite to control white rust disease in chrysanthemum. The research was conducted to evaluate several collected Cladosporium isolates against P. horiana, their parasitism mechanism and population dynamic in a production cycle. The experiment was carried out at the Indonesian Ornamental Crops Research Institute (IOCRI) from January to December 2015. Ten Cladosporium isolates with two synthetic fungicides and one negative control were designedly sprayed on chrysanthemum cv White Fiji. The results showed that Cladosporium isolates gave varied suppression to white rust intensity. Isolates HNC, DC, SGC and UC had higher parasitism and suppression intensities than other isolates and their effectiveness was the same as synthetic fungicides. Longer flower vase life was produced from Cladosporium and synthetic fungicide treated plants, while flower stalk and diameter were less affected by the Cladosporium applications. The population dynamic of Cladosporium was accordingly responded with the rust intensity in Cladosporium-treated plants. The parasitizing mechanism of Cladosporium to P. horiana was through teliospores envelopment resulted in the changes of teliospores morphology.